Measuring the e-service quality of Pakistani banks - Tahira, R.; Butt, Mohsin; De Run, E.; Ramay, A. (lnderscience Enterprises, 2012)
E-banking is a recent phenomenon in Pakistan and is a relatively less investigated topic of academic research. This paper sets out to investigate the dimension of e-service quality in Pakistani banks. A quantitative approach was used to identify and capture the e-service dimensions in the Pakistani banking sector. Data were analysed with the help of exploratory and confirmatory factor analysis. The results enable us to identify five dimensions of e-service quality in the Pakistani banking industry. Responsiveness, web interface, web quality, reliability and connectivity appear to be the most important dimensions of e-service quality for Pakistani banks.